Higher order thinking skills, school-based assessment and students’ mathematics achievement: Understanding teachers’ thoughts - Nurulwahida Azid; Ruzlan Md. Ali; Ihsana El Khuluqo; Sigid Edy Purwanto; Eka Nana Susanti (International Journal of Evaluation and Research in Education (IJERE), 2022)
The purpose of this study was to investigate the effect of incorporating higher order thinking skills (HOTS) in a school-based assessment (SBA) on mathematics achievement among students. A mixed-method case study design was used to assess a sample size of 158 students and three mathematics teachers. The students’ proficiency in mathematics was determined by using the standard based curriculum for secondary schools (kurikulum standard sekolah menengah/KSSM). Mathematics assessment paper that was assiduously organized by incorporating HOTS questions. The students’ thoughts on the incorporation of HOTS in the SBA were obtained through one-to-one face-to-face semi-structured interviews. The quantitative findings, which were analyzed using descriptive and regression tests, showed that 11.9% of the achieved mathematics score was contributed by incorporating HOTS in SBA, while 7.7% was contributed by SBA mastery level in mathematics. Students’ maturity and misconceptions about math are among the challenges in implementing HOTS in SBA. The challenges in applying HOTS in SBA had a positive effect on teachers’ pedagogical approach in a sense that they could devise a new strategy for meeting the needs of students and teach topics in alternative ways.